Bản đánh giá thủ tục hành chính dự án: Luật Quản lý, bảo vệ công trình quốc phòng và khu quân sự - Bộ Quốc phòng (2023)
Toàn văn Bản đánh giá thủ tục hành chính dự án: Luật Quản lý, bảo vệ công trình quốc phòng và khu quân sự.